Behavioural and cognitive mechanisms of Developmental Topographical Disorientation - Burles, Ford (Sci Rep, 2020)
Individuals affected by Developmental Topographical Disorientation (DTD) get lost on a daily basis, even in the most familiar of surroundings such as their neighbourhood, the building where they have worked for many years, and, in extreme cases, even in their own homes. Individuals with DTD report a lifelong selective inability to orient despite otherwise well-preserved general cognitive functions, and the absence of any acquired brain injury or neurological condition, with general intelligence reported to be within the normal range. To date, the mechanisms underlying such a selective developmental condition remain unknown. Here, we report the findings of a 10-year-long study investigating the behavioural and cognitive mechanisms of DTD in a large sample of 1211 cases. We describe the demographics, heritability pattern, self-reported and objective spatial abilities, and some personality traits of individuals with DTD as compared to a sample of 1624 healthy controls; importantly, we test the specific hypothesis that the presence of DTD is significantly related to the inability of the individuals to form a mental representation of the spatial surroundings (i.e., a cognitive map). We found that individuals with DTD reported relatively greater levels of neuroticism and negative affect, and rated themselves more poorly on self-report measures of memory and imagery skills related to objects, faces, and places. While performing interactive tasks, as a group, the individuals with DTD performed slightly worse on a scene-based perspective-taking task, and, notably struggled to solve tasks that demand the generation and use of a cognitive map. These novel findings help define the phenotype of DTD, and lay the foundation for future studies of the neurological and genetic mechanisms of this lifelong condition.